Doping effects of Ru on Sb2Te and Sb2Te3 as phase change materials studied by first-principles calculations. (June 2022) - Zhao, Zong-Yan; Peng, Shuo; Tan, Zhi-Long; Wang, Chuan-Jun; Wen, Ming
Abstract: In order to meet the requirements of phase change random access memory (PCRAM) for re-writing capability, stability and crystallization rate, phase change materials (PCMs) need to be optimized and modified. In the previous experimental work, we found that Ru doping can significantly improve the stability and reading/writing speed of Sb2 Te and Sb2 Te3 . In order to clarify the underlying physical mechanism of Ru doping effects on the improvement of PCRAM performance of Sb2 Te and Sb2 Te3, in this work, we further used the First-principles method to systematically calculate and analyze the crystal microstructure and electronic structure of Ru-doped Sb2 Te and Sb2 Te3 . In the crystal of Sb2 Te and Sb2 Te3, the substitution doping of Ru occupying the Sb site inside the [Sb2 Te3 ] penta-atomic layer is the most stable. Ru forms strong covalent bonds with Sb and Te in the matrix, which can improve the structural stability and crystallization temperature. The substitution doping of Ru at Sb site increases the band gap and carrier effective mass of Sb2 Te and Sb2 Te3, resulting in the increase of their resistivity. At the same time, this doping mode can also maintain the excellent rapid reversible phase transition properties of Sb2 Te and Sb2 Te3 . Graphical Abstract: ga1 Highlights: Ru impurity is most stable with substitutional doping occupying the Sb site inside the [Sb2 Te3 ] penta-atomic layer. Ru doping significantly decreases the interlayer spacing in the crystal microstructure of Sb2 Te and Sb2 Te3 . Ru doping only slightly changes the chemical bonding environment around it, and has no significant effect on remote atoms. Ru forms stronger covalent bonds with surrounding matrix atoms, improving the structural stability. Ru-substituted Sb doping can not only be easily realized, but also be very beneficial for improving the PCRAM performances.